Drug-induced diseases : prevention, detection, and management - Tisdale, James E.; Miller, Douglas A. (American Society of Health-System Pharmacists, 2010)
Discusses in detail, methods of identification, prevention, management of drug-induced diseases. Included will be discussions regarding specific information that should be provided to patients who may be receiving drugs that can cause diseases.